Zakłócenia pieniężne jako pierwotny czynnik sprawczy wahań koniunkturalnych - Leszek, Przemysław (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
The aim of this paper is to present a general overview of the problem of cyclical fluctuations in terms of the Austrian school of economics and to identify theoretical considerations leading to the argument included in its subject. The main economic issue of the theory is the efficient allocation of resources in the economy and their proper distribution between the competing processes of production and consumer needs. According to it, money disturbance affects the market processes, which is the reason for the erroneous distribution of available resources and causing the economic crisis. The main culprit is the monetary expansion, which started a string of events ultimately leading to changes in the real economy.
Keywords: monetary disruption; fluctuations; economic situation